A Review on Language, Power and Agency - Neupane, Binod (NELTA Bagmati Journal, 2022)
Language, power and agency are associated terminologies in the sense that power of language can influence others and construct reality. Similarly, agency uses the power of language to control and govern others by imposing ideology and knowledge. This paper aims to review how power and agency are associated with language and control others through language. Likewise, this paper critically analyses is how the power of language is responsible for social inequality. Since the nature of this paper is document analysis, I have reviewed available literature in various contexts including the concept of Foucault, Gramsci, Nietzsche, Derrida, Austin and Althusser; and show the relationship between language and power and the way how agency exercises power and reproduce inequality in society. The analysis of various studies reveals that language has the power to govern truth because the truth is the product of language games. Similarly, it shows that agency uses the power of language to dominate others such as male agency to dominate females, doctors and priest’s agency to control others through language. This paper is important to develop an analytical framework to illustrate the role of agency to impose the power of language to control various social activities.